Evaluasi Kebijakan Perdagangan Lobster yang Pro Nelayan di Provinsi Aceh - Vellayati Hajad; fadhil Ilhamsyah; Nurasma Aripin (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
The goal of this research is to evaluate the government's lobster business policies, particularly those that are aligned with the interests of fishermen (pro fishermen). Policy evaluation is critical in assessing the success of the lobster trade for the benefit of fishermen In this study, a qualitative method with a case study approach is used. Data was then gathered through observation, interviews, and supporting documentation. The informants interviewed in this study were chosen using snowball sampling based on their suitability with the required information. Informants include lobster catchers, traders, and local governments. The data is then analyzed using coding, categorization, comparison, and discussion research findings. The findings revealed that lobster trade policies were developed and implemented without the inclusion of fishermen as policy targets. As a result, they are excluded from existing policies and make it difficult for fishermen to find alternative sources of income. The failure of this policy is due to the following factors: (1) a lack of definitive data on lobster catching fishers; (2) an over-campaign concerning lobster availability in Simeulue.(3) There is no local government support for lobster cultivation efforts; (4) there is no socialization, coaching, equipment assistance, or capital injection; and (5) there is no local government support for carrier transportation modes.